Miswak in oral cavity - An update - Akhilanand Chaurasia; Ranjit Patil; Amit Nagar (Elsevier, 2013)
Miswak, scientifically known as Salvadora persica, is a species of Salvadora belonging to family Salvadoraceae. It is considered as "Nature's little toothbrush" as it is a popular chewing stick throughout Indian subcontinent. In India, it is commonly known as arak tree, meswak, peelu, kharjal or jhank. It also serves as a natural toothpaste with antibacterial, anti-caries, anti-periopathic disinfectant having anti-plaque and anti-fungal properties. Miswak sticks are being used by majority of people who cannot afford to buy the commercial western toothbrush and toothpaste mainly in rural areas of developing countries.The present review is an attempt to define the potential of the miswak in preventing and treating the common diseases of oral cavity and teeth.